Fully Percutaneous Fetoscopic Repair of Myelomeningocele: 30-Month Follow-up Data. Issue 6 (June 2021) - Diehl, D.; Belke, F.; Kohl, T.; Axt-Fliedner, R.; Degenhardt, J.; Khaleeva, A.; Oehmke, F.; Faas, D.; Ehrhardt, H.; Kolodziej, M.; Uhl, E.; Windhorst, A. C.; et al.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2021;57:113–118) The 2011 Management of Myelomeningocele Study (MOMS) reported improved postnatal outcomes for fetuses with myelomeningocele (MMC) who underwent intrauterine repair by open surgery, via hysterectomy, compared with those who underwent traditional postnatal surgery. The study found that the need for shunt decreased by 50% in children who underwent intrauterine repair.